The Effect of Math Anxiety On Mathematical Problem-Solving Ability - Christina Monika Samosir; Dadan Dasari (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
One of the factors that influence the ability to solve mathematical problems is that students do not like mathematics and lack the ability to understand concepts. The purpose of this study was to analyze the effect of math anxiety on students' mathematical problem solving abilities. This research uses SLR (Systematic Literature Review). The result of this study is that the effect of math anxiety on problem solving abilities is negative. Based on the studies reviewed, it can be concluded that the level of students' math anxiety is high, so the resulting problem-solving ability is low, and vice versa. Problem solving abilities are strongly influenced by students' math anxiety.